Preparation method of VOCs oxidation catalyst

Through the preparation of noble metal/heteropolyacid catalysts, combined with coating and modification treatment, the problems of low low temperature activity, poor high temperature thermal stability and poor humidity resistance are solved, and efficient VOCs treatment in high humidity environments are achieved.

CN119114164APending Publication Date: 2024-12-13CHINA ENERGY INVESTMENT CORP LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310698989.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing VOCs catalysts have low activity at low temperatures, poor thermal stability at high temperatures, and poor humidity resistance, which leads to the catalyst being easily deactivated and cannot effectively deal with VOCs pollution in high humidity environments.

Method used

The preparation method of noble metal/heteropolyacid catalyst is adopted. The precious metal is dispersed by combining noble metal with heteropolyacid, and the self-propagation method is used to increase the mechanical strength and stability, and the hydrophobicity of the catalyst is improved by coating the slurry and modified impregnation liquid. It can ensure that it is not covered by water molecules at low temperatures and extend its service life.

Benefits of technology

It improves the low-temperature activity and high-temperature thermal stability of the catalyst, enhances moisture resistance, extends the service life of the catalyst, and improves the redox nature of VOCs, reducing the ignition temperature and complete conversion temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114164A_ABST
    Figure CN119114164A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a VOCs oxidation catalyst, precious metal is dispersed in heteropolyacid through a self-propagating method, the activity of the precious metal is improved, and meanwhile, the cage-shaped structure of the heteropolyacid can be used as a supporting framework of the precious metal to improve the overall mechanical strength and stability of the catalyst; then the obtained powder catalyst and a second carrier are prepared into coating slurry together, cordierite is coated with the coating slurry through dipping, the coating is modified after drying, and therefore the competitive adsorption effect of water vapor on reaction gas on active sites is reduced, and the catalyst can be suitable for the VOCs treatment process with the high water content and the low operating temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field related to environmental protection, and also belongs to the technical field related to catalysts, and specifically relates to a method for preparing a VOCs oxidation catalyst. Background Art

[0002] Volatile Organic Compounds (VOCs) are a general term for organic compounds with a melting point below room temperature and a boiling point below 200-260°C under standard atmospheric pressure, mainly including alkanes, hydrocarbons, esters, alcohols, benzene series, etc. The anthropogenic sources of VOCs emissions mainly include fixed combustion sources, road mobile sources, industrial process sources, solvent use sources, etc. The petrochemical, coating, pharmaceutical, printing, pesticide, rubber and other industries will all produce VOCs waste gas during the use of organic solvents.

[0003] VOCs released into the atmosphere are very harmful to the environment, animals, plants and human health. They are an important precursor of photochemical smog and one of the recognized PM2.5 precursors. VOCs can irritate the skin, respiratory and blood systems, affect the heart and nervous system, and can even cause cancer.

[0004] Among the various common VOCs pollution control technologies, catalytic combustion has attracted attention due to its low operating cost, no secondary pollution, small combustion equipment, low reaction temperature, wide application range, and high VOCs removal rate. The key core of VOCs catalytic combustion technology is the catalyst. Since the entire airflow must be heated to a high temperature, generally far above 200°C, and when the temperature is too high, the catalyst is often more likely to sinter. Therefore, for the sake of safety, energy saving, low cost, and environmental protection, the catalytic oxidation reaction of VOCs is preferably carried out at low temperature. However, the actual flue gas composition contains a certain amount of water vapor, which is easy to condense in the micropores / mesopores of the catalyst in the low-temperature airflow, resulting in catalytic deactivation. If the hydrophobicity of the catalyst can be improved, the problem of deactivation caused by the active sites of the catalyst being covered when running at low temperatures can be avoided, and the service life of the catalyst can be extended.

[0005] CN107128932A discloses a method for preparing hydrophobic silica for VOC adsorption, which involves preparing a silica source, anhydrous ethanol and deionized water into a mixed liquid, then adding a composite coupling agent, filtering the gel after surface modification and solvent replacement, washing, and standing at room temperature; drying the washed gel, and then airflow ultrafine grinding to obtain a finished product.

[0006] CN109289509A discloses an indoor VOCs purification material for a high humidity environment and a preparation method thereof, which involves first preparing a phenolic aerogel with high porosity and adsorption, then preparing a silver-doped nano titanium dioxide photocatalyst, and then using a polymerization reaction of hexachlorocyclotriphosphazene and bisphenol AF to generate hydrophobic ring-crosslinked polyphosphazene microspheres. During the microsphere formation process, the photocatalyst is uniformly dispersed on the surface of the microspheres, and the microspheres are uniformly loaded on the surface of the aerogel, so as to obtain an indoor VOCs purification material for a high humidity environment.

[0007] The above-mentioned prior art involves VOCs adsorbents, which only adsorb VOCs gas through hydrophobic materials, but do not catalytically convert VOCs. Moreover, these materials are mainly used for the removal of indoor pollutants and for VOCs purification at room temperature. Therefore, as far as the catalysts used for catalytic oxidation of VOCs are concerned, there is still a continuous demand for improvement, such as improving the low-temperature activity of the catalyst, improving the high-temperature thermal stability of the catalyst, and improving the moisture resistance of the catalyst. Summary of the invention

[0008] In view of the problems existing in the above-mentioned prior art, the present invention provides a method for preparing a VOCs oxidation catalyst. The VOCs oxidation catalyst prepared thereby solves the problems of low low-temperature activity, poor high-temperature thermal stability and poor moisture resistance of the catalyst.

[0009] To achieve its purpose, the present invention adopts the following technical solutions:

[0010] In one aspect of the present invention, a method for preparing a VOCs oxidation catalyst is provided, comprising the following steps:

[0011] (1) Preparation of noble metal / heteropolyacid catalysts:

[0012] Mixing a soluble salt of a noble metal, a combustion agent, a heteropoly acid and water, stirring and drying to obtain a powder; grinding and calcining the powder to obtain a noble metal / heteropoly acid catalyst;

[0013] (2) Preparation of coating slurry:

[0014] The noble metal / heteropolyacid catalyst, carrier, inorganic binder and water obtained in step (1) are mixed and ground to obtain a coating slurry;

[0015] (3) Preparation of monolithic catalyst:

[0016] The cordierite is immersed in the coating slurry obtained in step (2), and after the immersion is completed, it is taken out and blown (for example, using a compressed air knife) until there is no pore blockage, and the slurry is preferably evenly distributed on the wall surface of the cordierite; the cordierite is placed upright along the direction of the pores, blown and dried (for example, using a hot drying gun), to obtain a monolithic catalyst;

[0017] (4) Catalyst modification:

[0018] The silane modifier, pore-forming agent, dispersant and water are uniformly sheared (for example, in a dispersing emulsifier) ​​to obtain a modified impregnation liquid; the monolithic catalyst obtained in step (3) is placed in the modified impregnation liquid for impregnation, and after the impregnation is completed, it is taken out and purged (for example, using a compressed air knife) until there is no pore blockage, and the modified impregnation liquid is preferably evenly distributed on the wall surface of the cordierite; the cordierite is placed upright along the direction of the pores, purged and dried (for example, using a hot drying gun) and calcined to obtain the VOCs oxidation catalyst.

[0019] In a specific embodiment of the present invention, in step (1), the noble metal is one or more of Pt, Pd and Rh. In the present invention, for the soluble salt of the noble metal, on the premise that the type of the noble metal is determined, the soluble salt thereof is well known in the art, such as nitrates of these noble metals.

[0020] In a specific embodiment of the present invention, in step (1), the combustion agent is one or more of urea, citric acid and glycine, preferably citric acid and / or glycine.

[0021] In a specific embodiment of the present invention, in step (1), the heteropolyacid is a non-P-containing heteropolyacid of Keggin-type structure, preferably silicotungstic acid and / or silicomolybdic acid, more preferably silicotungstic acid.

[0022] In a preferred embodiment of the present invention, in step (1), the molar ratio of the combustion agent to the precious metal is 1-4:1, preferably 2-3:1.

[0023] In a preferred embodiment of the present invention, in step (1), the mass ratio of the heteropolyacid to the soluble salt of the noble metal is 50-80:1, preferably 60-70:1.

[0024] In a specific embodiment of the present invention, in step (2), the carrier is alumina and / or titania.

[0025] In a specific embodiment of the present invention, in step (2), the inorganic binder is silica sol and / or alumina sol.

[0026] In a preferred embodiment of the present invention, in step (2), the noble metal / heteropolyacid catalyst accounts for 5-20% of the total mass of the coating slurry, preferably 10-15%.

[0027] In a preferred embodiment of the present invention, in step (2), the carrier accounts for 10-30% of the total mass of the coating slurry, preferably 15-20%.

[0028] In a preferred embodiment of the present invention, in step (2), the inorganic binder accounts for 2-10% of the total mass of the coating slurry, preferably 4-6%.

[0029] In a specific embodiment of the present invention, in step (4), the silane modifier is one or more of organosilane, organosiloxane and organosilazane, preferably one or more of methoxytrimethylsilane, ethoxytrimethylsilane and hexamethyldisiloxane.

[0030] In a specific embodiment of the present invention, in step (4), the pore-forming agent is hexadecyl ammonium bromide (CTAB) and / or polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123).

[0031] In a specific embodiment of the present invention, in step (4), the dispersant is one or more of polyvinyl pyrrolidone, polyethylene glycol and polyacrylamide.

[0032] In a preferred embodiment of the present invention, in step (4), the silane modifier accounts for 1-5% of the total mass of the modified impregnation solution, such as 2%, 3%, 4%, etc.

[0033] In a preferred embodiment of the present invention, in step (4), the mass ratio of the pore former to the silane modifier is 0.3-0.8:1, preferably 0.4-0.6:1.

[0034] In a preferred embodiment of the present invention, in step (4), the dispersant accounts for 0.2-0.8% of the total mass of the modified impregnation liquid, preferably 0.3-0.5%.

[0035] In a specific embodiment of the present invention, in step (1), the stirring temperature is 60-100°C, such as 70°C, 80°C, 90°C, etc.; the stirring time is 8-16h, such as 10h, 12h, 14h, etc.

[0036] In a specific embodiment of the present invention, in step (1), the drying temperature is 90-120°C, such as 100°C, 110°C, etc.; the drying time is 12-24h, such as 16h, 18h, 20h, etc.

[0037] In a specific embodiment of the present invention, in step (1), the purpose of grinding is to make the powder free of obvious lumps of solid. The specific grinding method and equipment can be reasonably selected by those skilled in the art.

[0038] In a specific embodiment of the present invention, in step (1), the calcination temperature is 350-450°C, such as 400°C, etc.; the heating rate is 3-6°C / min, such as 4°C / min, 5°C / min, etc.; the maximum calcination temperature holding time is 3-6h, such as 4h, 5h, etc.

[0039] In a specific embodiment of the present invention, in step (2), the grinding is performed by ball milling in a ball mill; preferably, the ball milling speed is 300-450 rpm, and the ball milling time is 30-90 min.

[0040] In a specific embodiment of the present invention, in step (2), ball milling is performed to make the particle size D(90) of the particles in the coating slurry less than 10 μm.

[0041] In a specific embodiment of the present invention, in step (3), the cordierite is immersed in the coating slurry for 5-15 minutes, such as 8 minutes, 10 minutes, 12 minutes, etc.

[0042] In a specific embodiment of the present invention, in step (3), the cordierite is placed vertically along the direction of the pores and then blown and dried at a temperature of 60-120°C, such as 80°C, 100°C, etc.

[0043] In a specific embodiment of the present invention, in step (4), the time for impregnation of the monolithic catalyst in the modified impregnation solution is 5-10 min, for example, 6 min, 7 min, 8 min, 9 min, etc.;

[0044] In a specific embodiment of the present invention, in step (4), the cordierite is placed vertically along the direction of the pores and then blown and dried at a temperature of 90-120°C, such as 100°C, 110°C, etc.

[0045] In a specific embodiment of the present invention, in step (4), the calcination procedure is as follows:

[0046] 25-120°C, heating rate is 1-10°C / min, preferably 5°C / min; 120°C is maintained for 2-4h, for example 3h;

[0047] 120-300°C, heating rate of 0.5-5°C / min, preferably 2°C / min; 300°C maintained for 4-6h, for example 5h;

[0048] 300-400°C, heating rate is 0.5-5°C / min, preferably 2°C / min; 400°C is maintained for 6-8h, for example 7h.

[0049] In another aspect of the present invention, it relates to a VOCs oxidation catalyst obtained by the above preparation method.

[0050] The present invention disperses a single layer of noble metal on the surface of heteropoly acid by self-propagating method to improve the activity of noble metal. Meanwhile, the cage structure of heteropoly acid can serve as the supporting skeleton of noble metal to improve the overall mechanical strength and stability of catalyst. Then the obtained powder catalyst and the second carrier are made into coating slurry, which is coated on cordierite by impregnation. After drying, the coating is hydrophobically modified to reduce the competitive adsorption of water vapor on reaction gas at active sites. The process is suitable for VOCs treatment process with high water content and low operating temperature.

[0051] By introducing precious metals into heteropolyacids, the precious metals are highly dispersed on the carrier surface and the valence state of the precious metal surface species is adjusted, which is conducive to the transformation of the precious metal active components to the oxidized state, which can improve the redox properties of the active center and reduce the ignition temperature and complete conversion temperature of the catalyst. In addition, by improving the hydrophobicity of the catalyst, the problem of deactivation caused by the active sites of the catalyst being covered by adsorbed water molecules when the catalyst is running at low temperatures can be avoided, thereby extending the service life of the catalyst.

[0052] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in the following aspects:

[0053] 1) Introducing noble metals into heteropolyacids so that the noble metal ions replace the hetero ions therein, achieving high dispersion of the noble metal ions and improving the low-temperature activity of the catalyst; the embedding of noble metal ions into heteropolyacids also enhances the interaction between the noble metal and the carrier and improves the high-temperature thermal stability;

[0054] 2) The coated monolithic catalyst is hydrophobically modified to solve the problem of catalyst deactivation caused by the active sites being easily covered by water molecules when the catalyst is running at low temperatures, making the catalyst highly resistant to moisture;

[0055] 3) Adding pore-forming agents to the hydrophobic modification reagent can ensure that VOCs molecules enter the catalyst pores for catalytic reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 The particle size distribution diagram of the particles in the coating slurry obtained in step (2) of Example 1 is shown. DETAILED DESCRIPTION

[0057] The present invention is further described below in conjunction with embodiments, but the present invention is not limited to the listed embodiments, and should also include equivalent improvements and modifications of the technical solutions defined in the claims attached to the present application.

[0058] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Other raw materials appearing in this article are conventional commercially available raw materials unless otherwise specified.

[0059] Test Method

[0060] Ethylene conversion test :

[0061] An experimental platform was built, and the catalysts prepared in the following examples and comparative examples (size 5*5*5cm) were selected and placed in a quartz tube fixed bed reactor. The ethylene conversion efficiency at each temperature point was tested after stabilization for 2h in the temperature range of 150-350°C (results are shown in Table 2). A simulated atmosphere (ethylene = 700ppm, O2 = 10%, H2O = 8%, N2 as the balance gas) was introduced, and the space velocity = 20000h -1 The concentration of ethylene at the catalyst inlet and outlet was tested by FTIR Fourier transform infrared flue gas analyzer (MKS, Multigas 6030).

[0062] Particle size testing :

[0063] The particle size and distribution were measured on a Mastersizer 2000E laser particle size analyzer from Malvern, UK. The sample was dispersed in deionized water and tested, and the corresponding particle size and distribution data were obtained after the test. The particle size D(90) represents the diameter corresponding to 90% of the cumulative distribution of particle size (0 to 100%).

[0064] Example

[0065] Example 1

[0066] (1) Take 10g of platinum nitrate, 12g of citric acid, and 600g of silicotungstic acid, add 300ml of deionized water, and stir at 80°C for 10h; place the obtained mixture in an oven at 110°C for 14h; grind the obtained dry powder until there is no obvious lump, place it in a muffle furnace with a heating rate of 5°C / min, and calcine at 400°C for 5h to obtain a noble metal / heteropoly acid catalyst;

[0067] (2) 20 g of noble metal / heteropoly acid catalyst, 30 g of alumina, 40 g of aluminum sol (20 wt%), and 60 g of deionized water were mixed evenly, placed in a ball mill and ball milled at 350 rpm for 90 min. After ball milling, the particle size D (90) was 6.01 μm (as shown in Table 1, the same below; the distribution was as shown in Table 1). Figure 1 As shown), a coating slurry is obtained;

[0068] (3) placing the cordierite in the above-mentioned coating slurry and immersing it for 10 minutes, taking it out and blowing it with a compressed air knife until there is no pore blockage, so that the slurry is evenly distributed on the cordierite wall; placing the cordierite upright along the direction of the pores, using a hot drying gun at 90°C to blow it until it is dry, to obtain a monolithic catalyst;

[0069] (4) Weigh 8 g of methoxytrimethylsilane and 4 g of P123, add 0.8 g of polyvinyl pyrrolidone and 160 g of deionized water, and shear them evenly in a dispersing emulsifier to obtain a modified impregnation solution; place the above-mentioned monolithic catalyst in the modified impregnation solution and immerse it for 8 minutes, take it out and blow it with a compressed air knife until there is no pore blockage; place the cordierite upright along the direction of the pores, and use a hot drying gun to blow it at 100° C. to dry it; the monolithic catalyst after blowing and drying is placed in a muffle furnace for calcination, and the calcination temperature curve is as follows:

[0070] 25-120℃, heating rate 5℃ / min; 120℃ for 4h;

[0071] 120-300℃, heating rate is 2℃ / min; 300℃ for 6h;

[0072] 300-400℃, heating rate is 2℃ / min; maintain at 400℃ for 6h.

[0073] Example 2

[0074] The catalyst was prepared by the same method as in Example 1, except that: in step (1), 10 g of platinum nitrate, 12 g of citric acid, and 650 g of silicomolybdic acid were added, 300 ml of deionized water were added, and the mixture was stirred at 70° C. for 10 h; the obtained mixture was placed in an oven at 110° C. and dried for 14 h; the obtained dry powder was ground until there was no obvious lump, placed in a muffle furnace with a heating rate of 5° C. / min, and calcined at 400° C. for 5 h to obtain a noble metal / heteropolyacid catalyst.

[0075] Example 3

[0076] The catalyst was prepared by the same method as in Example 1, except that in step (2), 20 g of noble metal / heteropoly acid catalyst, 30 g of alumina, 20 g of silica sol (20 wt%), and 60 g of deionized water were mixed evenly, placed in a ball mill and ball milled at 300 rpm for 30 min. After ball milling, the particle size D(90) was 9.16 μm, and a coating slurry was obtained.

[0077] Example 4

[0078] The catalyst was prepared by the same method as in Example 1, except that: in step (3), the cordierite was immersed in the coating slurry for 5 min, taken out and blown with a compressed air knife until there was no pore blockage, so that the slurry was evenly distributed on the cordierite wall; the cordierite was placed upright along the direction of the pores and blown with a hot drying gun at 110°C until it was dried to obtain an integral catalyst.

[0079] Comparative Example 1

[0080] The catalyst was prepared by the same method as in Example 1, except that the heteropoly acid in step (1) was replaced by an equal mass of aluminum oxide.

[0081] Comparative Example 2

[0082] The catalyst was prepared by the same method as in Example 1, except that after the monolithic catalyst was obtained in step (3), it was not impregnated in a modified impregnation solution and purged with a hot drying gun, but was directly placed in a muffle furnace for calcination.

[0083] Table 1 Particle size D (90) of the slurry after ball milling in step (2) of different embodiments and comparative examples

[0084] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 D(90) 6.01 7.16 9.16 7.85 7.28 7.35

[0085] Table 2 Ethylene conversion of catalysts of different embodiments and comparative examples at different temperatures

[0086] temperature Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 150℃ 42.3 32.8 36.2 30.2 15.4 9.5 165℃ 98.4 94.8 84.5 78.9 48.5 27.4 180℃ 99.0 98.7 98.8 98.3 95.7 86.3 200℃ 99.2 99.3 99.1 99.0 99.0 98.6 250℃ 99.4 99.3 99.2 99.1 99.2 99.1 300℃ 99.5 99.4 99.4 99.3 99.3 99.3 350℃ 99.5 99.4 99.4 99.3 99.4 99.4

[0087] Although the present invention has been described in detail for the purpose of illustration in the foregoing text, it should be understood that these detailed descriptions are only for illustration and can be modified by those skilled in the art without departing from the spirit and scope of the present invention. The present invention is limited only by the claims.

Claims

1. A method for preparing a VOCs oxidation catalyst, comprising the following steps: (1) Preparation of noble metal / heteropolyacid catalysts: Mixing a soluble salt of a noble metal, a combustion agent, a heteropoly acid and water, stirring and drying to obtain a powder; grinding and calcining the powder to obtain a noble metal / heteropoly acid catalyst; (2) Preparation of coating slurry: The noble metal / heteropolyacid catalyst, carrier, inorganic binder and water obtained in step (1) are mixed and ground to obtain a coating slurry; (3) Preparation of monolithic catalyst: The cordierite is placed in the coating slurry obtained in step (2) and immersed therein, and after the immersion is completed, it is taken out and purged until there is no pore blockage; the cordierite is placed upright along the direction of the pores, purged and dried, and a monolithic catalyst is obtained; (4) Catalyst modification: The silane modifier, pore-forming agent, dispersant and water are uniformly sheared to obtain a modified impregnation solution; the monolithic catalyst obtained in step (3) is placed in the modified impregnation solution for impregnation, and after the impregnation is completed, it is taken out and purged until there is no pore blockage; the cordierite is placed upright along the direction of the pores, purged, dried and calcined to obtain the VOCs oxidation catalyst.

2. The preparation method according to claim 1, wherein In step (1), The noble metal is one or more of Pt, Pd and Rh; The combustion agent is one or more of urea, citric acid and glycine, preferably citric acid and / or glycine; The heteropoly acid is a non-P-containing heteropoly acid of Keggin type structure, preferably silicotungstic acid and / or silicomolybdic acid, more preferably silicotungstic acid; Preferably, the molar ratio of the combustion agent to the precious metal is 1-4:1, preferably 2-3:1; Preferably, the mass ratio of the heteropolyacid to the soluble salt of the noble metal is 50-80:1, preferably 60-70:

1.

3. The preparation method according to claim 1, wherein In step (2), The carrier is alumina and / or titanium dioxide; The inorganic binder is silica sol and / or alumina sol; Preferably, the noble metal / heteropolyacid catalyst accounts for 5-20% of the total mass of the coating slurry, more preferably 10-15%; Preferably, the carrier accounts for 10-30% of the total mass of the coating slurry, more preferably 15-20%; Preferably, the inorganic binder accounts for 2-10% of the total mass of the coating slurry, more preferably 4-6%.

4. The preparation method according to claim 1, wherein In step (4), The silane modifier is one or more of organosilane, organosiloxane and organosilazane, preferably one or more of methoxytrimethylsilane, ethoxytrimethylsilane and hexamethyldisiloxane; The pore-forming agent is hexadecyl ammonium bromide and / or a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer; The dispersant is one or more of polyvinyl pyrrolidone, polyethylene glycol and polyacrylamide; Preferably, the silane modifier accounts for 1-5% of the total mass of the modified impregnation solution; Preferably, the mass ratio of the pore former to the silane modifier is 0.3-0.8:1, preferably 0.4-0.6:1; Preferably, the dispersant accounts for 0.2-0.8% of the total mass of the modified impregnation liquid, preferably 0.3-0.5%.

5. The preparation method according to any one of claims 1 to 4, wherein In step (1), The stirring temperature is 60-100°C and the stirring time is 8-16h; The drying temperature is 90-120℃ and the drying time is 12-24h; The calcination temperature is 350-450°C, the heating rate is 3-6°C / min, and the maximum calcination temperature holding time is 3-6h.

6. The preparation method according to any one of claims 1 to 4, wherein In step (2), The grinding is performed in a ball mill; preferably, the ball milling speed is 300-450 rpm, and the ball milling time is 30-90 min; more preferably, the ball milling makes the particle size D(90) in the coating slurry less than 10 μm.

7. The preparation method according to any one of claims 1 to 4, wherein In step (3), The time for the cordierite to be immersed in the coating slurry is 5-15 minutes; The cordierite is placed vertically along the direction of the pores and then blown and dried at a temperature of 60-120°C.

8. The preparation method according to any one of claims 1 to 4, wherein In step (4), The monolithic catalyst is immersed in the modified impregnation solution for 5-10 minutes; The cordierite is placed vertically along the direction of the pores and then blown and dried at a temperature of 90-120°C.

9. The preparation method according to any one of claims 1 to 4, wherein In step (4), the calcination procedure is as follows: 25-120℃, heating rate is 1-10℃ / min, 120℃ maintained for 2-4h; 120-300℃, heating rate 0.5-5℃ / min, 300℃ for 4-6h; 300-400℃, heating rate is 0.5-5℃ / min, keep at 400℃ for 6-8h.

10. The VOCs oxidation catalyst obtained according to the preparation method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Supported cobalt modified phosphorus molybdenum vanadium heteropolyacid catalyst and preparation method thereof

    CN120961201A